2005
DOI: 10.1124/jpet.105.089490
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction for Proteinase-Activated Receptor-2-Triggered Prostaglandin E2 Formation in Human Lung Epithelial Cells

Abstract: We investigated proteinase-activated receptor-2 (PAR 2 )-triggered signal transduction pathways causing increased prostaglandin E 2 (PGE 2 ) formation in human lung-derived A549 epithelial cells. The PAR 2 agonist, SLIGRL-NH 2 (Ser-Leu-Ile-Gly-Arg-Leu-amide), evoked immediate cytosolic Ca 2ϩ mobilization and delayed (0.5-3 h) PGE 2 formation. The PAR 2 -triggered PGE 2 formation was attenuated by inhibition of the following signal pathway enzymes: cyclooxygenases 1 and 2 (COX-1 and COX-2, respectively), cytoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
54
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 36 publications
(45 reference statements)
11
54
2
Order By: Relevance
“…Our signal transduction studies have shown that PAR2-triggered PGE 2 production involves formation of arachidonic acid via the MEK / ERK / cytosolic phospholipase A 2 (cPLA 2 ) pathway and upregulation of COX-2 via the Src / epidermal growth factor (EGF) receptor / p38 MAP kinase (p38MAPK) pathway in A549 cells (18,21). An independent study has also suggested possible involvement of the cAMP-response element-binding protein (CREB) pathway in the PAR2-mediated upregulation of COX-2 in the same cell line (22).…”
Section: Introductionmentioning
confidence: 99%
“…Our signal transduction studies have shown that PAR2-triggered PGE 2 production involves formation of arachidonic acid via the MEK / ERK / cytosolic phospholipase A 2 (cPLA 2 ) pathway and upregulation of COX-2 via the Src / epidermal growth factor (EGF) receptor / p38 MAP kinase (p38MAPK) pathway in A549 cells (18,21). An independent study has also suggested possible involvement of the cAMP-response element-binding protein (CREB) pathway in the PAR2-mediated upregulation of COX-2 in the same cell line (22).…”
Section: Introductionmentioning
confidence: 99%
“…Since the immediate product of the three types of COX catalyzed from AA was PGH 2 , the up-regulation of PGES expression is important in ensuring PGE 2 increase. PGES is an enzyme at the downstream of COX-2 pathway, and the expression of PGES often couples with that of COX-2 [12,13]. Based on the results in the present study, it could be deduced that, the up-regulation of COX-2 expression occurs first, and the up-regulation of PGES expression follows.…”
Section: Discussionmentioning
confidence: 58%
“…Factors related to the PAR-2 pathway are closely associated to inflammatory reactions and include prostaglandins, cytokines, growth factors and proteases, including matrix metalloprotease (MMP) and mast cell tryptase. [13][14][15][42][43][44] Activation of PAR-2 in various human cell lines upregulates COX-2 expression. [13][14][15] Nonsteroidal anti-inflammatory drugs, which can inhibit COX-2 activity, reduce the risks of several digestive diseases, including colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][42][43][44] Activation of PAR-2 in various human cell lines upregulates COX-2 expression. [13][14][15] Nonsteroidal anti-inflammatory drugs, which can inhibit COX-2 activity, reduce the risks of several digestive diseases, including colon cancer. 45 Yip-Schneider et al 46 reported that COX-2 inhibitors suppress pancreatic cancer cell growth and may be an effective treatment for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation